Eco-Consumerism in the Green Economy Era: A Systematic Literature Review of Drivers, Barriers, and Emerging Patterns - Lina Krisnawati (PT. Anagata Sembagi Education, 2026)
The transition toward a green economy has repositioned consumers as central agents of environmental change, giving rise to the phenomenon widely termed eco-consumerism. This conceptual, literature-based study examines how eco-consumerism manifests within the green economy era by synthesizing evidence from twenty-five peer-reviewed studies published between 2021 and 2026. Using a systematic literature review approach, the study traces the evolution of green purchase intention, eco-label trust, greenwashing skepticism, and digital-era green marketing strategies across diverse geographic and sectoral contexts. The findings indicate that eco-consumerism is shaped by an interaction of psychological antecedents such as environmental concern and perceived consumer effectiveness, social antecedents such as subjective norms and cultural orientation, and structural antecedents such as eco-label credibility and digital platform transparency. A persistent attitude-behavior gap remains evident despite rising environmental awareness, driven by price sensitivity, greenwashing fatigue, and inconsistent labeling standards. The novelty of this study lies in integrating three previously fragmented streams of literature, namely behavioral, marketing, and circular economy perspectives, into a unified framework that explains eco-consumerism under conditions of green economic transformation. Practical implications suggest that businesses and policymakers must move beyond promotional green claims toward verifiable and standardized sustainability communication to convert environmental concern into consistent green purchasing behavior. The article contributes a synthesized conceptual model intended to guide future empirical testing of eco-consumerism drivers in emerging green economies.